Vaccination of solid organ transplant candidates and recipients: Guidelines from the American society of transplantation infectious diseases community of practice. Issue 9 (5th June 2019) - Danziger‐Isakov, Lara; Kumar, Deepali; ,
Abstract: These updated guidelines of the AST IDCOP review vaccination of solid organ transplant candidates and recipients. General principles of vaccination as well as the use of specific vaccines in this population are discussed. Vaccination should be reviewed in the pre‐transplant setting and appropriate vaccines updated. Both inactivated and live vaccines can be given pre‐transplant. The timing of vaccination post‐transplant should be taken into account. In the post‐transplant setting, inactivated vaccines can be administered starting at 3 months post‐transplant with the exception of influenza which can be given as early as one month. Inactivated vaccines can be safely administered post‐transplant. There is accumulating data that live‐attenuated vaccines can also be given to select post‐transplant patients. Close contacts of transplant patients can receive most routine live vaccines. Specific vaccines including pneumococcal, influenza, hepatitis B, HPV, and meningococcal vaccines are discussed. Newer vaccines for seasonal influenza vaccine and herpes zoster are highlighted. Live‐attenuated vaccines such as measles, mumps, rubella, and varicella are also discussed. Emerging data on live‐attenuated vaccines post‐transplant are highlighted.